Advances on molecular phylogeny and classification of the genus Trichoderma and its related teleomorphs - ZHANG Chu-long; XU Tong (浙江大学学报. 农业与生命科学版)
Since Rifai bring forwarded the first classification of the genus Trichoderma in 1969, the great advances on molecular phylogeny and classification of the genus Trichoderma and it's related teleomorphs have achieved and made considerable change in classification especially in recent years. The paper reviews the recent advances on molecular phylogeny and classification of this field.